(untitled) (Ames, Iowa, 2006)
This book provides the most comprehensive collection of timely information regarding Mycobacterium bovis in any single source. This international reference includes the most current information on mechanisms of virulence of tubercle bacilli and immunologic and biochemical responses of the host involved in resistance. The book includes information on the diagnosis and application of the latest molecular techniques in epidemiologic investigations. Included are chapters on the economic impact of outbreaks of M. bovis in alternate species on control programs in domestic animals
Keywords: Trực khuẩn Mocobacterium bovis,Tuberculosis,Tuberculosis in cattle,Mocobacterium bovis,Bệnh lao,Bệnh lao trong gia súc